Características estruturais da oferta de café em Minas Gerais - Ladeira, Heloísa Helena; Brandt, Sérgio Alberto; Aad Neto , Alexandre; Guilhon de Castro, Flávio; Oliveira, Marcília B M (Revista Ceres, 2025)
This study, coming from secondary time series data from 1947 to 1970, intended to analyze the supply of coffee in Minas Gerais, determining the variables that influence decisions of farmers concerning the quantity of the cropped acreage, as well as identifying the physical and economic variables which affect. yield. From the responses concerning cropped acreage and yield a supply relationship was determined for the state. The models were adjusted by the least squares method and the adopted criterion for selection of the models that explain variation in cropped area and yield was based upon the “t” test, coeficient of determination (Ro) and the “F” test. The problem of serial correlation among the residues was analyzed by the Durbin-Watson statistic helped by “h” test of Durbin and p, the Theil-Nagar statistic.